Spinal muscular atrophy type I associated with a novel SMN1 splicing variant that disrupts the expression of the functional transcript - Votsi, Christina; Koutsou, Pantelitsa; Ververis, Antonis; Georghiou, Anthi; Nicolaou, Paschalis; Tanteles, George; Christodoulou, Kyproula (Frontiers in Neurology, 2023)
Introduction Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by pathogenic variants in the SMN1 gene. The majority of SMA patients harbor a homozygous deletion of SMN1 exon 7 (95%). Heterozygosity for a conventional variant and a deletion is rare (5%) and not easily detected, due to the highly homologous SMN2 gene interference. SMN2 mainly produces a truncated non-functional protein (SMN-d7) instead of the full-length functional (SMN-FL). We hereby report a novel SMN1 splicing variant in an infant with severe SMA. Methods MLPA was used for SMN1/2 exon dosage determination. Sanger sequencing approaches and long-range PCR were employed to search for an SMN1 variant. Conventional and improved Real-time PCR assays were developed for the qualitative and quantitative SMN1/2 RNA analysis. Results The novel SMN1 splice-site variant c.835-8_835-5delinsG, was identified in compound heterozygosity with SMN1 exons 7/8 deletion. RNA studies revealed complete absence of SMN1 exon 7, thus confirming a disruptive effect of the variant on SMN1 splicing. No expression of the functional SMN1-FL transcript, remarkable expression of the SMN1-d7 and increased levels of the SMN2-FL/SMN2-d7 transcripts were observed. Discussion We verified the occurrence of a non-deletion SMN1 variant and supported its pathogenicity, thus expanding the SMN1 variants spectrum. We discuss the updated SMA genetic findings in the Cypriot population, highlighting an increased percentage of intragenic variants compared to other populations.